Impact of glossopharyngeal insufflation and complete exhalation on breath-hold performance and physiological parameters in elite skin divers - Bourdas, D. I.; Geladas, N. D. (European Journal of Applied Physiology, 2024)
Purpose This study examined the physiological responses of ten elite divers to normal breathing (BHn), glossopharyngeal inhalation (BHi), and complete exhalation (BHe) prior to five maximal breath-hold (BH) efforts.